Prenatal Yoga untuk Mengurangi Nyeri Pinggang pada Ibu Hamil Trimester III - Febriana Dewi, Riski; Shofia Luthfiyati Annisa, Siti; Christiani, Ninik (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2025)
Pregnancy in the third trimester is characterized by significant physiological and anatomical changes that may lead to musculoskeletal discomfort, particularly lower back pain. This condition is commonly experienced by pregnant women due to postural changes, increased body weight, and hormonal influences such as relaxin, which affects joint and ligament stability. Lower back pain during pregnancy can reduce mobility, disrupt sleep, increase stress levels, and negatively impact the overall quality of life of pregnant women. Therefore, effective and safe non-pharmacological interventions are needed to address this issue. This community service program aimed to reduce lower back pain and improve knowledge among third-trimester pregnant women through the implementation of prenatal yoga at Klinik Sehat Sidamukti, Sidamukti Village, Patimuan District. The intervention consisted of health education regarding the causes and impacts of lower back pain during pregnancy, followed by guided prenatal yoga sessions focusing on stretching, breathing techniques, and relaxation. The activity involved ten third-trimester pregnant women and was conducted through several stages, including preparation, implementation, evaluation, and follow-up. Pain intensity was measured using a pain scale before and after the intervention, while participants’ knowledge was assessed through pre-test and post-test questionnaires. The results showed a significant decrease in lower back pain intensity after the intervention. Prior to prenatal yoga, all participants experienced moderate to severe pain. Following the intervention, all participants reported mild pain levels. Additionally, participants’ knowledge regarding prenatal yoga improved from 89.5% in the pre-test to 100% in the post-test. These findings indicate that prenatal yoga is an effective non-pharmacological intervention to reduce lower back pain and enhance knowledge among pregnant women in their third trimester. Integrating prenatal yoga into routine antenatal care is recommended to promote maternal comfort and well-being.   Abstrak Kehamilan trimester ketiga merupakan periode yang ditandai dengan peningkatan pertumbuhan janin dan perubahan fisiologis yang signifikan pada tubuh ibu. Perubahan postur tubuh, peningkatan berat badan, serta pengaruh hormon relaksin sering menimbulkan keluhan muskuloskeletal, terutama nyeri pinggang bawah. Nyeri pinggang merupakan salah satu keluhan paling umum pada ibu hamil trimester III dan dapat berdampak pada penurunan kualitas hidup, gangguan tidur, keterbatasan aktivitas, serta meningkatnya stres dan kecemasan. Oleh karena itu, diperlukan intervensi non-farmakologis yang aman, efektif, dan mudah diterapkan untuk mengurangi keluhan tersebut. Salah satu metode yang dapat digunakan adalah prenatal yoga. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mengurangi nyeri pinggang serta meningkatkan pengetahuan ibu hamil trimester III melalui penerapan prenatal yoga di Klinik Sehat Sidamukti, Desa Sidamukti, Kecamatan Patimuan. Metode yang digunakan meliputi edukasi kesehatan mengenai nyeri pinggang pada kehamilan, praktik prenatal yoga yang dipandu oleh tenaga kesehatan, serta evaluasi menggunakan pengukuran skala nyeri dan tingkat pengetahuan sebelum dan sesudah intervensi. Peserta kegiatan berjumlah 10 ibu hamil trimester III. Hasil kegiatan menunjukkan adanya penurunan intensitas nyeri pinggang yang signifikan. Sebelum intervensi, seluruh peserta berada pada kategori nyeri sedang hingga berat, sedangkan setelah intervensi, seluruh peserta mengalami nyeri ringan. Selain itu, tingkat pengetahuan ibu hamil mengenai manfaat dan penerapan prenatal yoga juga mengalami peningkatan, dari 89,5% pada pre-test menjadi 100% pada post-test. Kesimpulannya, prenatal yoga efektif sebagai intervensi non-farmakologis untuk mengurangi nyeri pinggang sekaligus meningkatkan pengetahuan ibu hamil trimester III. Kegiatan ini diharapkan dapat diintegrasikan ke dalam pelayanan antenatal sebagai upaya promotif dan preventif untuk meningkatkan kesehatan ibu dan janin.